Exploring Translanguaging and Trans-semiotizing for Students with Intellectual Disabilities - Damayanti, Siti Alpiyah; Yannuar, Nurenzia; Zubaidi, Nanang; Khaerani, Nadya Shifa (LPPM Universitas Advent Indonesia, 2026)
This study explores translanguaging and trans-semiotizing in employment, benefits and challenges, and situations facilitated or hindering the learning process in special needs education for students with intellectual disabilities in Indonesia. This research conducted a case study on two English teachers in SLBN 3 Banjarmasin. With a qualitative approach, with data collected through semi-structured interviews and classroom observations on intellectual disabilities classroom, for the junior high school. Results from two teachers show that both teachers use three languages; Banjar (local language), Indonesian, and English. They also employ various semiotic modes to increase students’ understanding, create a comfortable learning environment, and reduce academic pressure. The challenges faced by teachers include differences in mother tongue between teachers and students, spent time in lesson preparation and implementation. In conclusion, translanguaging and trans-semiotizing help students who have difficulty understanding vocabulary. However, excessive use without careful planning or without balancing verbal and non-verbal modes, makes students completely dependent on their mother tongue and semiotic signs, this can actually hinder verbal language skills and hinder students' progress in learning the target language.